IoT Based Monitoring System Using MQTT Protocol on Tortilla Chips Cutting Machine - Thayyib, Ahmad Reza; Salamah, Irma; R.A., Halimatussa’diyah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
This research focuses on monitoring and controlling a tortilla chip-making machine using the MQTT protocol. Tortilla chips are a popular snack made from corn tortillas that are cut into triangles and fried or baked. The study utilizes the Internet of Things concept, where sensors are integrated into the machine to enable data exchange and communication through networks. The MQTT protocol is chosen due to its lightweight nature, making it suitable for resource-constrained devices and efficient in IoT applications. The research involves using ESP32 as the microcontroller and various sensors, such as ZMPT101b, ACS712, Tachometer, and HC-SR04. The data collected from the sensors is transmitted to a Thingspeak channel via MQTT, allowing real-time monitoring and control of the machine. The results show that the MQTT protocol effectively facilitates communication of the tortilla chip cutting machine, with satisfactory delay and data integrity. The tortilla chip cutting test was successful, producing triangular-shaped chips. Overall, the research concludes that the implementation of the MQTT protocol in the IoT-based tortilla chip-making machine is effective and reliable. The results of this study indicate that the average delay in data communication is 2.8 seconds, and the integrity testing revealed a 3% error in the accuracy of the sensor data.